Предмет: Математика,
автор: katialebedinec
помогите доказать!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ:
3(a-b)+2(a+b-c)+b-3c=3a-3b+2a+2b-2c+b-3c=5a+0-5c=5a-5c=5(a-c)
Автор ответа:
1
Ответ:
3(x-b)+2(a+b-c)+b-3c =5(x-c)
3x-3b+2a+2b+2c+b-3c =5x-5c
3x+0+2a-c =5x-5c
3x+2x =5x-5c
3x-5x = -5c-2a+c
-2x = -4c-2a
x =2c+a
Похожие вопросы
Предмет: Английский язык,
автор: керимлинезрин
Предмет: Русский язык,
автор: Эвелина2015
Предмет: Английский язык,
автор: AMYLETMINORALBA13
Предмет: Математика,
автор: Ksu22022007
Предмет: Математика,
автор: AmangeldievaDanara